The effects of C5aR antagonism on histopathological and blood parameters changes following chlorhexidine-induced contact dermatitis in mice - Siong, Jing Jing (2015)
For decades, chlorhexidine has been used in the medical field for its disinfectant properties. Yet, chlorhexidine is found to illicit hypersensitivity reactions in human, but whether it can produce the same reaction in animals remain unclear. In this study, we investigate the effects of C5aR antagonism on histopathological and blood parameters changes following chlorhexidine-induced contact dermatitis in mice. Mice were randomly divided into four groups for chlorhexidine induced contact dermatitis and given treatments of Dexamethasone, Histamil, complement component C5a receptor antagonist PMX205 and saline. Blood samples were taken for haematology while skin samples were taken for histopathology analysis. The viability of serum IgE for allergy reaction is detected by ELISA technique. Results obtained from the study indicate that treatment of chlorhexidine-induced contact dermatitis by C5aR antagonist has managed to reduce the severity of the lesions similar to anti-histamine and corticosteroid treatment based on the gross skin lesion scoring and histopathological evaluation. The blood parameters did not showed any significant changes compared to normal. As a summary, C5aR antagonism provides an alternative towards the treatment of chlorhexidine-induced contact dermatitis.